2020
DOI: 10.1029/2020ja028192
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Formed Wedge‐Like Structures of Different Ion Species Deep in the Inner Magnetosphere

Abstract: • Large-amplitude low-frequency (around 0.1 Hz) plasma density fluctuations are observed at comet 67P • They coincide with the plasma density and magnetic field enhancements surrounding the diamagnetic cavity • This is a new type of waves at comets, probably ion Bernstein waves, possibly driven by velocity space anisotropies arising near the cavity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 166 publications
2
19
0
Order By: Relevance
“…In this paper, we revisit the Van Allen Probes A and B observations of wedge‐like ion spectral structures previously reported in Ren et al (2020). The observations, also shown in Figures 1 and 2, suggest that the inner edge of the structure appears at L ∼ 3 within a specific energy range of several keV.…”
Section: Summary and Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In this paper, we revisit the Van Allen Probes A and B observations of wedge‐like ion spectral structures previously reported in Ren et al (2020). The observations, also shown in Figures 1 and 2, suggest that the inner edge of the structure appears at L ∼ 3 within a specific energy range of several keV.…”
Section: Summary and Discussionmentioning
confidence: 65%
“…However, their drift speeds are very low (mostly below 1 km/s, especially for the ions with μ=12 eV/nT; see the blue drift paths in Figure 3b), and the ion locations change very slightly in the next 7 hr (from the time of convection reduction to the observation time of the wedge‐like structures; see the minor difference between the distributions of the circles and the solid dots in Figure 3b and 3d). In other words, the wedge‐like structures deform very slowly after the reduction of magnetospheric convection, which provides a large time window for their observations in the nightside inner magnetosphere (Ren et al, 2020).…”
Section: Simulation and Interpretationsmentioning
confidence: 99%
“…Ren et al. (2020) also found that these structures depended on substorm activities, and suggested that the source of wedge‐like structures was probably the nightside substorm injection. The wedge‐like structures reported in Ren et al.…”
Section: Introductionmentioning
confidence: 96%
“…In the inner magnetosphere, many spacecraft have detected a variety of ion spectral structures, which are named after the shapes of the energy bands or gaps for ion fluxes in the energy‐time (or energy‐ L shell) spectrograms. These structures include the nose‐like structures (e.g., Ferradas et al., 2016; Smith & Hoffman, 1974), the wedge‐like structures (Ren et al., 2020; Zhou et al., 2020), the finger‐like structures (Denton et al., 2016; Wang et al., 2020), the trunk‐like structures (Zhang et al., 2015), and the ion spectral gaps (e.g., Kovrazhkin et al., 1999; Shirai et al., 1997; Yue et al., 2021). Among these ion spectral structures, the nose‐like structures were first reported in the 1970s (Smith & Hoffman, 1974) and since then have been most extensively investigated via both spacecraft observations and simulations (Ebihara et al., 2004; Ejiri et al., 1980; Ferradas et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several spacecraft missions in the inner magnetosphere have indeed detected various features in ion energy‐time spectrograms, which are named after the characteristic shapes of energy bands or gaps of ion fluxes. These spectral features include the “nose‐like” structures (e.g., Buzulukova, Kovrazhkin, et al., 2003; Ebihara, Ejiri, et al., 2004; Fennell et al., 1998; Ferradas et al., 2016a, 2016b; Ganushkina et al., 2001; Li et al., 2000; Smith & Hoffman, 1974; Vallat et al., 2007), the “wedge‐like” dispersions (e.g., Ebihara, Yamauchi, et al., 2001; Ren et al., 2020; Zhou et al., 2020), the “trunk‐like” structures (Zhang et al., 2015), and ion spectral gaps (e.g., Buzulukova, Galperin, et al., 2002; Fennell et al., 1981; Kaye et al., 1981; Kistler et al., 1989; Kistler & Mouikis, 2016; Kovrazhkin et al., 1999; Lennartsson et al., 1979; Shirai et al., 1997). As expected, statistical studies of ion spectral features have reported their dependence on geomagnetic conditions.…”
Section: Introductionmentioning
confidence: 99%